Comparison of methods for the quantification of cell-free DNA isolated from cell culture supernatant - Abel Jacobus Bronkhorst; Vida Ungerer; Stefan Holdenrieder (Tumor Biology)
Gaining a better understanding of the biological properties of cell-free DNA constitutes an important step in the development of clinically meaningful cell-free DNA–based tests. Since the in vivo characterization of cell-free DNA is complicated by the immense heterogeneity of blood samples, an increasing number of in vitro cell culture experiments, which offer a greater level of control, are being conducted. However, cell culture studies are currently faced with three notable caveats. First, the concentration of cell-free DNA in vitro is relatively low. Second, the median amount and size of cell-free DNA in culture medium varies greatly between cell types. Third, the amount and size of cell-free DNA in the culture medium of a single cell line fluctuates over time. Although these are interesting findings, it can also be a great source of experimental confusion and emphasizes the importance of method optimization and standardization. Therefore, in this study, we compared five commonly used cell-free DNA quantification methods, including quantitative polymerase chain reaction, Qubit Double-Stranded DNA High Sensitivity assay, Quant-iT PicoGreen Assay, Bioanalyzer High Sensitivity DNA assay, and NanoDrop One c . Analysis of the resulting data, along with an interpretation of theoretical values (i.e. the theoretical detection and quantification limits of the respective methods), enables the calculation of optimal conditions for several important preanalytical steps pertaining to each quantification method and different cell types, including the (1) time-point at which culture medium should be collected for cell-free DNA extraction, (2) amount of cell culture supernatant from which to isolate cell-free DNA, (3) volume of elution buffer, and (4) volume of cell-free DNA sample to use for quantification.